Possible Indications of Variations in the Directionality of Beta-Decay Products - Sturrock, Peter A.; Fischbach, Ephraim; Piatibratova, Oksana; Scholkmann, Felix (Frontiers in Physics, 2021)
Some experiments seem to yield strong evidence of variability of beta-decay rates, but other experiments may show little or no such evidence. Some recent experiments help clarify the situation. In particular, a certain oscillation appears in neutrino measurements made at the Super-Kamiokande Neutrino Observatory and in radon beta-decay measurements made at the Geological Survey of Israel, with identical frequency (9.43 years−1), amplitude and phase, strengthening the case for an influence of neutrinos on beta decays. A review of current experimental information leads us to suggest that 1) beta-decay rates do not change, but 2) the angular distribution of decay products may be anisotropic, and 3) the angular distribution of decay products may be influenced by the ambient neutrino flux. It appears that experiments at standards laboratories tend to be insensitive to direction, and this may be the reason that they tend not to exhibit evidence of variability.